Evaluating the Influence of Digital Marketing, Service Quality, and Product Excellence on Loyalty Through the Mediating Role of Customer Satisfaction - Qashmal, Muhammad; Adam, Muhammad; Nizam, Ahmad (Heca Sentra Analitika, 2024)
This study investigates the effects of digital marketing, service quality, and product excellence on customer loyalty, with customer satisfaction serving as a mediating variable. Focusing on Bank Aceh Syariah (BAS) in Aceh Province, Indonesia, this research uses a Structural Equation Modeling (SEM) approach and reveals that both service quality and digital marketing significantly enhance customer satisfaction at BAS, while product excellence does not exhibit a similar influence. Further analysis demonstrates that customer satisfaction positively impacts customer loyalty. Interestingly, digital marketing, service quality, and product excellence do not directly affect customer loyalty; however, customer satisfaction partially mediates the relationship between service quality and customer loyalty. These findings underscore the critical importance of digital marketing and service quality in fostering customer satisfaction and promoting customer loyalty. For banks aiming to enhance loyalty, the study highlights the necessity of robust digital marketing strategies and superior service quality. While product excellence is important for meeting customer needs, it appears less significant in driving satisfaction and loyalty compared to service quality and digital marketing. By prioritizing these areas, BAS can achieve higher levels of customer satisfaction, leading to sustained customer loyalty.